PENGEMBANGAN E-BOOK BAHASA ARAB DENGAN APLIKASI KVISOFT FLIPBOOK MAKER PADA SISWA KELAS XI KEAGAMAAN MAN 1 SLEMAN - Huda, Nurul; Al Fariz, Thoriq Zia; Handayani, Eka Utari (Ijaz Arabi Journal of Arabic Learning, 2021)
This research is the development of a digital-based e-book with the kvisoft flipbook maker application as an alternative medium for learning Arabic. This study uses a 4D development model: define, design, develop and disseminate. The instrument used to analyze student responses was a Guttman scale questionnaire consisting of agreeing or disagree. The data analysis technique used is qualitative and quantitative. The results of this study are the use of the kvisoft flipbook maker application as a medium for developing e-books. Language is in the excellent category. The result of the score of the Arabic language teacher is 3.81, the material expert is 3.87, and the media expert is 3.93. The limited field trial response results with an ideal score of 85.71% and are included in the category agreement. The results of the comprehensive field trial reached an ideal score of 97.80% and were included in the agreed category. This e-book contains Arabic learning materials, including videos, audios, and GIFs, to facilitate students' understanding of Arabic material while supporting students' listening and speaking skills training.